Loss of CXCR5 expression and monocyte epithelial–mesenchymal transition are blood‐borne signatures of sterile granulomatous diseases - Yuwei Hao; Anthea Anantharajah; Jane M Wells; Lyndell L Lim; Anthony JH Hall; Gary YJ Chew; Matthew C Cook (Clinical & Translational Immunology, 2025)
Abstract Objectives Sarcoidosis is the exemplar sterile granulomatous disease and can affect any organ system. Tattoo uveitis (TU) resembles sarcoidosis clinically and histologically but is distinguished by the absence of systemic lymphadenopathy, with inflammation restricted to skin and eyes. In this study, our objectives were, first, to resolve whether TU is a subset of sarcoidosis or a different antigen‐driven condition and, second, by comparing TU and sarcoidosis, to identify blood‐borne signatures of active and quiescent sterile granulomatous diseases. Methods We recruited patients with active and inactive TU, sarcoidosis and healthy controls on whom we performed blood cell phenotyping and transcriptomics. Results Unlike sarcoidosis, active TU is characterised by marked CXCR5 down‐regulation on B cells and CD4+ T cells that normalises on remission. TCR‐VDJ sequencing reveals an antigen‐driven response in sarcoidosis, but not in TU, with clonally expanded cytotoxic and terminally differentiated CD8+ effectors. Both active TU and sarcoidosis exhibit gene signatures of epithelial‐to‐mesenchymal transition (EMT) in circulating monocytes, whereas epithelioid macrophages are a hallmark of active granulomas. Conclusion We have identified both shared and specific phenotypes in TU and sarcoidosis. Marked CXCR5 down‐regulation occurs in active TU and could explain the unique absence of lymphadenopathy. Both TU and sarcoidosis are characterised by inflammatory monocyte phenotypes and transcriptional signatures of EMT.